SIRFIDOS AFIDOFAGOS (DIPTERA, SYRPHIDAE): IDENTIFICACIÓN RÁPIDA A CAMPO DE ESTADOS PREIMAGINALES Y LISTA DE ENEMIGOS NATURALES DE LAS ESPECIES MÁS FRECUENTES EN CEREALES Y FORRAJES EN LA PROVINCIA DE BUENOS AIRES (ARGENTINA) - Greco, Carlos F. (Acta Entomológica Chilena, 2022)
Keys to preimaginal stages of the five species of aphidophagous syrphids more frequenly found in differents crops and pastures in Argentina: Allograpta exótica (Wied.), Syrphus phaeostigma Wied., Platycheirus stegnus Say, Pseudodorus clavatus (Fabricius) and Ocyptamus argentinus (Curran), were made for a quick identification of these species in ecological studies. It was not possible to make keys to eggs since these are not easily separated with a naked eye. Both larvae and pupae present stable color patterns characteristics of each species and in the case of larvae, characteristics patterns of each instar inside each species. The following natural enemies were found in the surveys: one entomopathogen (Entomophtora muscae), four parasitoids (Diplazon laetatorius (Fabricius), Callaspidia sp., Encyrtus sp. and an egg parasitoid) and a predator spider, Thomisus sp. (Araneae, Thomisidae).